Influence of large-scale asperities on the shear strength of concrete-rock interface of small buttress dams. (15th October 2021) - Sas, Gabriel; Popescu, Cosmin; Bista, Dipen; Seger, Andreas; Arntsen, Bård; Johansson, Fredrik; Lia, Leif
Highlights: Scaled model of pillar of a plate dam was tested in the lab. Full field measurement of strain was done using DIC. The failure occurred in the dam concrete in the models with high angled asperity. Large scale high angled asperity act as shear key in dams. Shear capacity of dam increased by 10 folds when full geometry of dam was considered. Abstract: This paper presents an investigation of the influence of large-scale asperities on the shear strength of four physical models of a pillar (also known as buttress web) from Kalhovd dam in Norway. The objective was to observe the structural behaviour of the pillar under design and ultimate loading scenarios and to compare results of the tests with those of nonlinear finite element analysis (FEA) and standard guideline methods. Four models at 1:5 scale were prepared with different interface profiles and tested. The results from model test and the results of a benchmarking process carried out with nonlinear FEA are presented. Furthermore, the FEA was expanded to other hypothetical scenarios to extend understanding of effects of the locations and inclinations of large-scale asperities on the sliding stability of concrete dams. The results are compared with those obtained using standard design methods and estimated safety factors are presented.